Does Vitamin D Level Affect the Radiographic Severity of Osteoarthritis Knee and its Functional Status? - S. Hariprasad; Aditya Seth; S. J. Karthik; Anish N. Tawde; Ratnakar Vecham; Adarsh Annapareddy; A. V. Gurava Reddy; Rajat Jain (Journal of Orthopedics, Traumatology and Rehabilitation)
Objective: The objective of this study was to investigate the relationship between Vitamin D levels, radiographic severity, and functional status in patients with primary knee osteoarthritis (OA). Materials and Methods: A cross-sectional study was conducted on 71 patients with primary knee OA. Clinical and radiological evaluations were performed to confirm the diagnosis of knee OA. Vitamin D levels were measured, and radiographic severity was assessed using the Kellgren–Lawrence grading system. Functional status was evaluated using Lequesne’s indices. Statistical analyses were conducted to compare variables between patients with deficient Vitamin D levels (<30 ng/mL) and those with normal levels (≥30 ng/mL). Results: The study population had a mean age of 59.39 ± 8.09 years, with a majority of females (80.3%). The mean Vitamin D level was 19.22 ± 6.086 ng/mL, and 91.5% of patients were classified as Vitamin D deficient. Radiographic evaluation revealed joint space narrowing in all patients, with 87.3% having moderate-to-severe narrowing. Osteophytes were observed in 53.5% of patients. While there were no significant differences in demographic and radiographic variables based on Vitamin D levels, a significant association was found between functional grading and normal Vitamin D levels. Conclusion: This study highlights a high prevalence of Vitamin D deficiency in patients with knee OA. Although there was no significant association between Vitamin D deficiency and radiographic severity, Vitamin D levels were found to influence the functional status of the knee. Further research with larger sample sizes and longitudinal designs is necessary to establish a comprehensive understanding of the relationship between Vitamin D levels and knee OA severity.